RESEARCH ON THE SIMULATION OF THE OPERATION OF ROBOTIC MECHANISMS - Georgeta Toma (Romanian Journal of Petroleum & Gas Technology)
The optimal design of the structures from the component of the robotic mechanisms requires a good knowledge of the various parameters during their operation. Among them are mentioned the working parameters that give the position, speed and acceleration at the operational level of the robots, as well as at the level of the active joints from the component of the robotic mechanisms. This paper presents how a functional simulator of robotic active mechanisms called RobSim was created. The simulator allows the positional and kinematic analysis of active robotic mechanisms, regardless of their configuration and the number of component modules. The positional analysis is performed parametrically. A polynomial variation of the fifth degree was considered for the position parameters at the level of active joints. The simulator allows establishing the position and orientation at the operational level of the analyzed robotic mechanism, as well as the trajectory followed by the robot during operation. Also, the simulator allows establishing the speeds and accelerations both at the operational level of the robotic mechanisms, as well as at the level of the active joints in their component.